NILAI-NILAI PENDIDIKANTAUHID DALAM KELUARGA (Analisis Terhadap Surah Al-Baqarah Ayat 132-133 Dalam Tafsir Ibnu Katsir) - Suci Rahmatika (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2016)
The purpose of this study is to reveal about: 1) Description and analysis of the values ​​of monotheism education in the family according to Surah Al-Baqarah Verses 132-133, 2) Description and analysis of monotheism education in the family according to Tafsir Ibn Kathir. 3) Describe and the relevance of the values ​​of monotheism education in the family according to Surah Al-Baqarah Verse 132-133 in today's life. This study uses a qualitative approach and the type of library research (library research). The data collection technique begins with collecting literature. In this study, the work of the character in question is the book of Ibn Kathir al Damsyiqi, Tafsir al Qur'an al-'Adzhim, Juz I, (Riyadh: Dar Thoyibah li Nasyr wa Tawzi‟, 1999) cet. I, also by M. Abdul Ghoffar, Tafsir Ibnu Katsir, Bogor: Imam Shafi'i Library. 2004. Browsed the works of others about the character in question or on the topic under study (as secondary data). The latter can be found in encyclopedias, systematic and thematic books. Because the book usually shows a wider library.